Benefits Of Sukuk For Infrastructure Development In Papua - Fitria Pangesti; Dewi Shinta Nuriyah; Siti Nur Haliza (PAPUA: International Journal of Sharia Business Management, 2024)
Sukuk are certificates that present proof of ownership which is divided into tangible assets, benefit value, services or ownership of project assets or investment activities. Issuance of Sukuk for general state financing purposes or financing specific projects, such as the construction of alrenative roads, airports, educational facilities and hospitals. This journal will focus on the benefits of sukuk for the development of Eastern Indonesia and aims to understand the impact and benefits of sukuk issuance in the context of economic and infrastructure development in the Eastern Indonesia region, especially Papua. It is stated in Law Number 19 of 2008 concerning State Sharia Securities, SBSN or State Sukuk, namely state securities whose issuance is based on sharia principles, is proof of participation in SBSN assets, both in rupiah and foreign currency. In general, there are several types of sukuk, namely: Mudharabah Sukuk, Murabahah Sukuk, Musyarakah Sukuk, Salam Sukuk, Istishna Sukuk, Ijarah Sukuk. The rate of economic growth and investment in a country or region cannot be separated from the availability of infrastructure such as transportation, telecommunications, sanitation and energy. This causes infrastructure development to become the foundation of sustainable economic development. Sukuk are starting to be used to finance government projects in various countries and one of them is in Eastern Indonesia, such as alternative roads, namely the Youtefa Bay Bridge and Siboru Airport in Nabire, West Papua.